(untitled) (Latakia University Journal -Medical Sciences Series, 2023)
OBJECTIVES: THIS STUDY AIMS TO COMPARE FRACTURE RESISTENCE BETWEEN TWO ROTARY FILES TO ELECT THE BETER SYSTEM TO USE IN CLINICAL PRACTICE MATERIALS AND METHODS: 40 SANE MAXILLARY FIRST PREMOLARS WITH TWO CANALS WERE COLLECTED, THEN THE CROWNS WERE CUT 1 MM ABOVE THE CEJ. THIS SPECIMEN WAS PREPARED BY HAND FILES FROM FANTA UNTILE REACHING FILE 0.04 / 25 INSIDE ACRYLIC MODELS. THE SPECIMENS WERE RANDOMLY DISTRIBUTED INTO TWO EQUAL GROUPS , EACH GROUP CONTAINS 20 TEETH, THE FIRST GROUP WAS PREPARED BY RAMO RAINBOW FILES FROM RAMO, THE SECOND GROUP WAS PREPARED BY PROTAPER GOLD FILES FROM DENTSPLY. A TEST WAS CONDUCTED TO COMPARE FRACTURE RESISTANCE FOR BOTH KINDS AND DEFINE THE BETTER FILE. RESULTS: THE CONTROL GROUP OF RAMO ROTARY FILES SHOWED SIGNIFICANTLY HIGHER FRACTURE RESISTANCE THAN THE EXPERIMENTAL GROUP BUT THIS DID NOT APPLY TO THE CONTROL GROUP OF PROTAPER. RAMO ROTARY FILES SHOWED SIGNIFICANTLY HIGHER FRACTURE RESISTANCE THAN PROTAPER ROTARY FILES FOR BOTH CONTROL AND EXPERIMENTAL GROUPS. CONCLUSIONS: FRACTURE RESISTANCE OF RAMO ROTARY FILES WITHOUT PREVIOUS PREPARATION IS BETTER THAN THOSE AFTER USING TWICE. FRACTURE RESISTANCE OF RAMO ROTARY FILES IS BETTER THAN THOSE OF PROTAPER REGARDLESS OF PREVIOUS PRAPARATION OR AFTER USING TWICE.